In-hospital outcome of Fascicular block following ST elevated Acute Myocardial Infarction - Ali, Md Ashraf; Alo, Dilara; Uddin, Mir Jamal (KYAMC Journal, 2017)
Objective: The aim of the study was to observe the magnitude of in-hospital morbidity and mortality in fascicular block following ST elevated acute myocardial infarction (AMI). Background: Fascicular block following ST elevated acute myocardial infarction is often seen in CCU. It predicts poorer in-hospital outcome and signifies underlying extensive myocardial damage with jeopardized conducting system. Materials and Methods: This prospective case control observational study was carried out among the S-T elevated AMI patients in the CCU of NICVD during the period of January 2004 to December 2004. One hundred consecutive patients of first attack of AMI with or without fascicular block were included in this study. The patients suffering from congenital heart disease, cardiomyopathies, valvular heart disease and the patients having permanent pacemaker or preexisting syndrome were excluded from the study. Fifty numbers of patients suffering newly diagnosed fascicular block with acute AMI was considered as case and equal number of patients without fascicular block was taken as control. Case selection was done with the help of history, physical examination, twelve leads surface ECG and echocardiography. In hospital outcome was observed in terms of morbidity and mortality. So, hospitalized patents were followed up daily both clinically and with bedside continuous ECG monitoring. Results: In- hospital mortality was 30% in AMI with fascicular block and 12% in AMI without fascicular block, the difference was statistically significant (p=0.027). In hospital morbidity was significantly higher (70%) in cases compared to control (40%). The relative risk indicates that in hospital complications were 2.97 times higher in patients complicated with fascicular block. The mean number of composite complications (CCF, complete heart block, cardiogenic shock, VT, VF, ejection fraction and haemodynamic status etc.) was 1.14+1.0 in comparison to. 64 .85 in control group and mean difference was statistically significant (P<0.001). The mean percentage of ejection fraction was 44.9+5.2 in case of study group and it was 48.4+ 4.3 in control group. Mortality among fascicular blocks with anterior AMI was highest (24%). It was highest (80%) in LBBB and lowest in RBBB (14.3%). Conclusion: Fascicular block following AMI was associated with higher complications and mortality rate. So the physicians should be more aware of the aggressive management of the patients with fascicular block found in AMI. KYAMC Journal Vol. 5, No.-1, Jul 2014, Page 467-471